Can Leflunomide Play a Role in Cytomegalovirus Disease Prophylaxis besides its Antirheumatic Effects?. Issue 1 (January 2015) - Lu, Cheng-Hsun; Tsai, Jia-Huei; Wu, Mu-Zon; Yu, Chia-Li; Hsieh, Song-Chou
Leflunomide, a disease-modifying antirheumatic drug (DMARD), has shown effectiveness in many autoimmune disorders and can suppress cytomegalovirus (CMV) disease in humans. Thus, it is possible for leflunomide to play a role in CMV prophylaxis or preemptive therapy in high-risk patients in addition to its application as a DMARD for autoimmune disorders. We describe two adult patients who developed CMV disease after administration of low-dose leflunomide. One patient was successfully treated with an increasing leflunomide dosage, resulting in a long-term suppression of serum CMV viral load.